Hybridized Time Series Modeling with Machine Learning Techniques for Pomegranate Price Fluctuations - S. Vishnu Shankar; Rajeev Ranjan Kumar; Mrinmoy Ray; V. Lavanya; R. Subash (Agricultural Research, 2026)

Evaluation of gamma irradiation effect on morpho-physiological and biochemical traits of dragon fruit (Selenecereus monacanthus) under water stress environment - Kuldeep K. Shukla; Kundan Kishore; K. Pradhan; Subash C. Swain; Manas R. Sahoo; Rajkumari Bhol; S. Samal; Ankita Sahu; Ashok Mishra (Plant Physiology Reports, 2025)

Influence of Temperature on Physiological Responses of Nannochloropsis gaditana Isolated from Southeastern Coastal Waters of India - M. J. Thamarai Selvi; V. Rani; P. Padmavathy; A. Uma; R. Shalini; B. Sivaraman; P. Subash; Rishikesh Venkatrao Kadam (Thalassas: An International Journal of Marine Sciences, 2025)

Yesterday’s extremes, today’s new normal: flood risk in the Kathmandu Valley, Nepal - Rocky Talchabhadel; Jeeban Panthi; Vishnu P. Pandey; Biplob Rakhal; Ganesh R. Ghimire; Sunil Bista; Saurav Bhattarai; Subash Poudel; Yogesh Bhattarai; Rajaram Prajapati; Bhesh R. Thapa; Bikash Nepal; et al. (Natural Hazards, 2025)

K-means Pelican Optimization Algorithm based Search Space Reduction for Remote Sensing Image Retrieval - W. T. Chembian; G. Senthilkumar; A. Prasanth; R. Subash (Journal of the Indian Society of Remote Sensing, 2025)

Fostering effective and sustainable scientific collaboration and knowledge exchange: a workshop-based approach to establish a national ecological observatory network (NEON) domain-specific user group - Alison Donnelly; Ankur R. Desai; Katherine A. Heckman; Lucas E. Nave; Michael J. Cramer; Marie Faust; Peter Weishampel; Caleb Slemmons; Christian G. Andresen; Edward Ayres; Stacy R. Cotey; Kathryn M. Docherty; et al. (International Journal of Biometeorology, 2024)
The decision to establish a network of researchers centers on identifying shared research goals. Ecologically specific regions, such as the USA’s National Ecological Observatory Network’s (NEON’s) eco-climatic domains, are ideal locations by which to assemble researchers with a diverse range of expertise but focused on the same set of ecological challenges. The recently established Great Lakes User Group (GLUG) is NEON’s first domain specific ensemble of researchers, whose goal is to address scientific and technical issues specific to the Great Lakes Domain 5 (D05) by using NEON data to enable advancement of ecosystem science. Here, we report on GLUG’s kick off workshop, which comprised lightning talks, keynote presentations, breakout brainstorming sessions and field site visits. Together, these activities created an environment to foster and strengthen GLUG and NEON user engagement. The tangible outcomes of the workshop exceeded initial expectations and include plans for (i) two journal articles (in addition to this one), (ii) two potential funding proposals, (iii) an assignable assets request and (iv) development of classroom activities using NEON datasets. The success of this 2.5-day event was due to a combination of factors, including establishment of clear objectives, adopting engaging activities and providing opportunities for active participation and inclusive collaboration with diverse participants. Given the success of this approach we encourage others, wanting to organize similar groups of researchers, to adopt the workshop framework presented here which will strengthen existing collaborations and foster new ones, together with raising greater awareness and promotion of use of NEON datasets. Establishing domain specific user groups will help bridge the scale gap between site level data collection and addressing regional and larger ecological challenges.

Application of airborne and ground geophysics to unravel the hydrogeological complexity of the Deccan basalts in central India - Sahebrao Sonkamble; Subash Chandra; Paras R. Pujari (Hydrogeology Journal, 2022)

Environmental influence on bacterial efficiency in ensuring self-healing mortars - Poornima V; Venkatasubramani R; Sreevidya V; Sruthy Subash; Jayanarayanan Karingamanna (European Journal of Environmental and Civil Engineering, 2022)

Influence of Different Nutrient Management Practices and Cropping Systems on Organic Carbon Pools in Typic Ustochrept Soil of Indo-Gangetic Plains in India - Debashis Dutta; A. L. Meena; Amit Kumar; N. Subash; R. P. Mishra; P. C. Ghasal; Jairam Choudhary; Chandra Bhanu; Raghavendra KJ; Chetan Kumar G; Ankur Kumar; Vaibhav Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Milk yield, composition, and lactation curve models of Bargur cattle under farmers’ production system in their native habitat - P. Ganapathi; R. Venkataramanan; Vrinda B. Ambike; R. Subash (Tropical Animal Health and Production, 2022)

Transport and fate of microplastics in wastewater treatment plants: implications to environmental health - Subash Raju; Maddison Carbery; Aswin Kuttykattil; Kala Senathirajah; S. R. Subashchandrabose; Geoffrey Evans; Palanisami Thavamani (Reviews in Environmental Science and Bio/Technology, 2018)

Topical application of polyethylenimine as a candidate for novel prophylactic therapeutics against genital herpes caused by herpes simplex virus - Kyoko Hayashi; Hiroki Onoue; Kohei Sasaki; Jung-Bum Lee; Penmetcha K. R. Kumar; Subash C. B. Gopinath; Yoshie Maitani; Takashi Kai; Toshimitsu Hayashi (Archives of Virology, 2014)

Excitotoxicity in the Pathogenesis of Autism - M. M. Essa; N. Braidy; K. R. Vijayan; S. Subash; G. J. Guillemin (Neurotoxicity Research, 2013)

Climate agreements and India: aligning options and opportunities on a new track - P. R. Shukla; Subash Dhar (International Environmental Agreements: Politics, Law and Economics, 2011)

Antioxidant Effect of Caffeic Acid on Oxytetracycline Induced Lipid Peroxidation in Albino Rats - R. Jayanthi; P. Subash (Indian Journal of Clinical Biochemistry, 2010)

Double trisomy with 48, XXX+21 karyotype in a Down’s syndrome child from Jammu and Kashmir, India - Wahied Khawar Balwan; Parvinder Kumar; T. R. Raina; Subash Gupta (Journal of Genetics, 2008)